Risk of binge eating behavior among university women, quality of their diet and their perception of their body image - Shah, Ami Y.; Nigudkar, Madhuri (World Nutrition, 2025)
BackgroundBinge eating disorder (BED) is an emerging public health concern, particularly among young adult women.ObjectiveThis study aimed to evaluate the relationship between BED risk and key behavioral and psychological factors - specifically, dietary quality, physical activity, and body image perception - among university-going women in Mumbai.MethodsA cross-sectional study was conducted among 100 female students aged 18–25 years. Binge eating risk was assessed using the Binge Eating Scale. Dietary intake was measured through 24-hour recall and diet quality evaluated using the Global Diet Quality Score. Body image was assessed using the Body Image Questionnaire, while physical activity was evaluated using the International Physical Activity Questionnaire–Short Form. Anthropometric measurements were recorded, and statistical analyses, including Pearson’s correlation, ANOVA, and chi-square tests, were conducted using SPSS v20.ResultsFifteen percent of participants showed moderate BED risk, and another fifteen percent showed severe risk. BED risk positively correlated with daily energy (r = 0.821, p < 0.05), carbohydrate (r = 0.903, p < 0.01), and fat intake (r = 0.936, p < 0.01), while negatively correlating with diet quality (r = -0.354, p < 0.01), physical activity levels (r = -0.226, p < 0.05), and body image satisfaction (r = -0.323, p < 0.01).ConclusionsThe study highlights that higher BED risk is significantly associated with poor diet quality, lower physical activity, and body dissatisfaction. These findings underscore the importance of multi-dimensional interventions that address both nutritional and psychological aspects of binge eating behavior among young adult women.